BMPR-1B, BMP-15 and GDF-9 genes structure and their relationship with litter size in six sheep breeds reared in Egypt - Ahmed. A. Saleh (BMC Research Notes, 2020)
Abstract Objective The aim of this work was to investigate three different mutations; Fec-B, FecXG, Fec-GH at three candidate genes; Bone morphogenetic protein receptor IB, Bone morphogenetic protein 15 and Growth Differentiation Factor 9, respectively, in six sheep breeds reared in Egypt namely; Rahmani, Barki, Rahmani X Barki cross, Awassi, Awassi X Suffolk cross, and Ossimi and their association with litter size. Results Genomic DNA of 132 sheep was investigated for the Fec-B, FecXG, and Fec-GH mutations by Restriction Fragment Length Polymorphism, Single-Stranded Conformation Polymorphism and DNA sequencing. The results revealed that all breeds did not carry Fec-B mutation. On the other side, the mutations of FecXG, and Fec-GH were detected in Rahmani, and Rahmani X Barki cross which is associated with the high twinning rate/litter size of Rahmani (1.28) and Rahmani X Barki cross (1.22). While, the average litter size for other breeds had almost a constant values rate over six parities, ranging between 1.00 and 1.04.